A Multicenter Study of Preventable Contact Burns From Glass Fronted Gas Fireplaces. Issue 1 (January 2015) - Wibbenmeyer, Lucy; Gittelman, Michael A.; Kluesner, Karen; Liao, Junlin; Xing, Yunfan; Faraklas, Iris; Anyan, Walter; Gamero, Chelsea; Moulton, Steven; Nederveld, Cindy; Banks, Ashley; Ryan, Colleen M.; et al.
<x xml:space="preserve">Abstract</x> Glass fronted gas fireplaces (GFGFs) have exterior surfaces that can reach extremely high temperatures. Burn injuries from contact with the glass front can be severe with long-term sequelae. The Consumer Product Safety Commission reported that these injuries are uncommon, whereas single-center studies indicate a much higher frequency. The purpose of this multi-institutional study was to determine the magnitude and severity of GFGF injuries in North America. Seventeen burn centers elected to participate in this retrospective chart review. Chart review identified 402 children ⩽10 years of age who sustained contact burns from contact with GFGF, who were seen or admitted to the study hospitals from January 2006 to December 2010. Demographic, burn, treatment, and financial data were collected. The mean age of the study group was 16.8 ± 13.3 months. The majority suffered burns to their hands (396, 98.5%), with burns to the face being the second, much less common site (14, 3.5%). Two hundred and sixty-nine required rehabilitation therapy (66.9%). The number of GFGF injuries reported was 20 times greater than the approximately 30 injuries estimated by the Consumer Product Safety Commission's 10-year review. For the affected children, these injuries are painful, often costly and occasionally can lead to long-term sequelae. Given that less than a quarter of burn centers contributed data, the injury numbers reported herein support a need for broader safety guidelines for gas fireplaces in order to have a significant impact on future injuries.